Implementasi Tim Asesmen Terpadu (Tat) Dalam Penentuan Status Hukum Dan Rehabilitasi Penyalahguna Narkotika Oleh Badan Narkotika Nasional Provinsi Lampung - Helin Kristikaningwulan; Bambang Hartono; Suta Ramadan (Jurnal Ilmiah Wahana Pendidikan, 2026)
Drug abuse is a serious problem affecting legal, health, and social aspects, requiring both repressive approaches through criminal law enforcement and rehabilitative approaches focused on the recovery of physical, psychological, and social conditions. Law Number 35 of 2009 on Narcotics mandates medical and social rehabilitation for drug abusers and addicts. This provision is operationalized through the Integrated Assessment Team (Tim Asesmen Terpadu/TAT), regulated under the Joint Regulation of Seven Ministries/Institutions (2014) and the Head of the National Narcotics Board Regulation No. 11 of 2014. This study examines the implementation of TAT in determining legal status and rehabilitation recommendations for drug abusers at the National Narcotics Board of Lampung Province and identifies obstacles in practice. Using normative juridical and empirical methods, data were collected through literature review and interviews. Findings indicate that TAT implementation generally aligns with regulations and effectively promotes a humane, recovery-oriented approach. However, challenges remain, including limited rehabilitation facility capacity, differing perceptions among law enforcement regarding TAT recommendations, and restricted supervision over implementation. Strengthening inter-agency coordination and enhancing rehabilitation support are essential to ensure TAT’s effectiveness and sustainability.